Welfare impact of globalization in developing countries: Examining the mediating role of human capital - Olagunju, Kehinde Oluseyi; Ogunniyi, Adebayo; Oguntegbe, Kunle Francis; Raji, Ibrahim Oluwole; Ogundari, Kolawole (MDPI, 2019)
Despite remarkable progress in the fight against poverty during the past few decades, the proportion of the poor living in developing countries is still on the high side. Many countries have promoted integration as an important development strategy; however, its impact on welfare of the poor is still unclear. In this study, we examine the roles of education and health dimensions of human capital in globalization and its impact on the poverty gap and the child mortality rate using cross-country panel data covering 110 developing countries between 1970 and 2015. We use a model based on system generalized method of moments (SGMM) to control for unobserved heterogeneity and potential endogeneity of the explanatory variables. The empirical results reveal that globalization reduces poverty gap and child mortality rate, and that an increase in the stock of human capital in developing economies improves welfare outcomes. The study also finds that human capital strengthens the negative impact of globalization on poverty gap and child mortality rate. For example, should enrollment in secondary school in Nigeria (in 2013) be increased from 39.2% to 61.6%, on average, it could translate into 2508 fewer under-five child deaths. We recommend that interconnectedness and promotion of human capital development should constitute a fundamental component of policy mix targeted at enhancing reduction of poverty and child mortality rate in developing countries.